Status of Scake Fishing Gear Technology in Cirebon Waters - Bayyinah, Auliya Al; Sandisasmita, Pramuji; Nurkhasanah, Devi (Journal La Lifesci, 2024)
This study aims to evaluate the status of the technology of the rake fishing gear used in Cirebon waters. This evaluation is important to understand the effectiveness and environmental impacts of the fishing gear in local fisheries activities. The research method used involves a descriptive approach with primary data collection through direct observation in the field and interviews with local fishermen. In addition, secondary data was obtained from literature and related reports relevant to the use of rake fishing gear. The results of the study indicate that the technology of the rake fishing gear in Cirebon waters has certain characteristics that affect the catch and sustainability of marine resources. This study also found that although this fishing gear is efficient in catching fish, its use requires better management to minimize negative impacts on the marine ecosystem.